KECENDERUNGAN PENERIMAAN OPINI AUDIT GOING CONCERN: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Siregar, Baldric; Rahman, Abdul (Jurnal Riset Akuntansi dan Keuangan, 2012)
This research provides the investigation over the acceptance of going concern audit opinion  which can be performed by observing the company’s internal condition such as the audit  quality, company’s financial condition, audit opinion prior year, company growth, company  size, and debt to equity ratio. Samples are obtained by purposive sampling method and 185 observation data from 2006 - 2010 at manufacturing companies listed at Indonesia Stock Exchange. The logistic regression used to examine the factors that are predicted to affect the probability of acceptance of going concern audit opinion. The result of this research is that audit opinion prior year, company growth, and debt to equity ratio are significantly affect the probability of acceptance of going concern audit opinion. On the other hand audit quality, company’s financial condition, and company size do not significantly acceptance of going concern audit opinion.Keywords: audit quality, financial condition, growth, going concern, going concern opinion